Caracterização dos peptídeos indicadores de degradação do colágeno, N-acetyl-PGP e PGP, na saliva e urina de pacientes com doença pulmonar obstrutiva crônica - Rodrigues, Sara Fernanda Albuquerque (2011)
The Chronic Obstructive Pulmonary Disease (COPD) is characterized by a chronic limitation of the airflow and an abnormal inflammatory lung response to particles or harmful gases. The COPD is associated with an intense degradation of the extracellular matrix components (ECM) such as the Collagen fibers and Elastin, caused by the imbalance of enzymes in the parenchymal pulmonary. Reports show that the Collagen Hydrolysis produce peptides that are biologically actives (N-acetyl-PGP and PGP) that induces the neutrophil chemo-taxes through the interaction among the receptors CXCR1 and CXCR2 in the bronchoalveolar lavage fluid, and in the blood of the patients with COPD. Objective: To analyze the presence of the N-acetyl-PGP and PGP peptides as specifics indicators of the collagen degradation on the patients with COPD versus the healthy individuals. Methods: The Experiment was done with 25 individuals, grouped under patients with COPD (n=16) and healthy individuals (n=9). After the initial procedures for this experiment, all participants were submitted to the Spectrometric Test. The six-minute walking test is followed by urine and saliva gathering. The qualitative and comparative analysis of the N-acetyl-PGP and PGP in the saliva and urine of the participants on the experiment was made by the signals founded on the mass obtained by the MALDI-TOF/LC-MS/MS. Results: The degradation of the peptides of the collagen, N-acetyl-PGP and PGP, were identified on the samples of urine, 81.2% and 68.7% of the patients with COPD, respectively. Therefore, on the control group, the presence of 11.1% of N-acetyl-PGP and the absence of PGP were identified in the urine of the participants. In the samples of the peptide fractions of the saliva of both groups, the N-acetyl-PGP and PGP were not identified. Conclusion: The presence of N-acetyl-PGP and PGP in the urine of patients with COPD support the hypothesis of the existence of other products of degradation of the components of the ECM yet not identified. Probably only founded in patients with COPD that would help to add information on the diagnostic for the COPD.